Childhood apraxia of speech - Rutkiewicz-Hanczewska, Małgorzata (Papers in Linguistics, 2020)
The article is concerned with the specificity of childhood apraxia of speech, i.e. a disorder affecting the ability to transform an abstract phonological code into speech movement. Such disorders affect mainly planning and/or programming of motor sequences, which results in inconsistent linguistic errors, disrupted transitions between segments of speech, and inappropriate prosody. The author presents features that distinguish apraxia of speech, pointing also to the underlying cause of the disorder, which has not been recognised yet, and its possible neurobiological substrates. In the second part of the text, the focus is on the specificity of the therapy of verbal apraxia, with particular emphasis on the methods available in Polish speech and language therapy.